2020
DOI: 10.1186/s40792-020-00981-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy for a cholelithiasis patient with an aberrant biliary duct of B5: a case report

Abstract: Background An aberrant biliary duct of segment 5 (B5) is a rare anomaly of the biliary tract. All anatomical anomalies of the biliary tract are risk factors for bile duct injury during surgery. We report a case of cholelithiasis with an aberrant B5 that was detected during a detailed preoperative imaging examination and treated with laparoscopic cholecystectomy. Case presentation A 69-year-old woman was admitted to the emergency room of our hospital with abdominal pain. She was diagnosed with cholelithiasis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…A study conducted in India also found chronic cholecystitis to be the most frequent histopathologic diagnosis established after cholecystectomy for cholelithiasis. In another study the most common age group affected was between 40-49 years corresponding with our findings 13,14 . Another study in a tertiary care hospital to study histopathological spectrum of gallbladder disease also found chronic cholecystitis to be the most frequent post surgically established histopathologic diagnosis after cholelithiasis 15,16 .…”
Section: Resultssupporting
confidence: 91%
“…A study conducted in India also found chronic cholecystitis to be the most frequent histopathologic diagnosis established after cholecystectomy for cholelithiasis. In another study the most common age group affected was between 40-49 years corresponding with our findings 13,14 . Another study in a tertiary care hospital to study histopathological spectrum of gallbladder disease also found chronic cholecystitis to be the most frequent post surgically established histopathologic diagnosis after cholelithiasis 15,16 .…”
Section: Resultssupporting
confidence: 91%